22.6k views
5 votes
Let f(x)=5x-4 and g(x)=x^2-1. Find (g o f)(0)

User Manoj Sahu
by
5.2k points

1 Answer

3 votes

Answer: 15

==============================

Work Shown:


(g \circ f)(x) = g(f(x))\\\\g(x) = x^2-1\\\\g(f(x)) = (f(x))^2-1\\\\g(f(x)) = (5x-4)^2-1\\\\g(f(0)) = (5*0-4)^2-1\\\\g(f(0)) = (-4)^2-1\\\\g(f(0)) = 16-1\\\\g(f(0)) = 15\\\\(g \circ f)(0) = 15

User Jannell
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.